Metaproteomics and metabolomics analyses of chronically petroleum‐polluted sites reveal the importance of general anaerobic processes uncoupled with degradation. Issue 20 (27th August 2015) - Bargiela, Rafael; Herbst, Florian‐Alexander; Martínez‐Martínez, Mónica; Seifert, Jana; Rojo, David; Cappello, Simone; Genovese, María; Crisafi, Francesca; Denaro, Renata; Chernikova, Tatyana N.; Barbas, Coral; von Bergen, Martin; et al.
<x xml:space="preserve">Abstract</x> Crude oil is one of the most important natural assets for humankind, yet it is a major environmental pollutant, notably in marine environments. One of the largest crude oil polluted areas in the word is the semi‐enclosed Mediterranean Sea, in which the metabolic potential of indigenous microbial populations towards the large‐scale chronic pollution is yet to be defined, particularly in anaerobic and micro‐aerophilic sites. Here, we provide an insight into the microbial metabolism in sediments from three chronically polluted marine sites along the coastline of Italy: the Priolo oil terminal/refinery site (near Siracuse, Sicily), harbour of Messina (Sicily) and shipwreck of MT Haven (near Genoa). Using shotgun metaproteomics and community metabolomics approaches, the presence of 651 microbial proteins and 4776 metabolite mass features have been detected in these three environments, revealing a high metabolic heterogeneity between the investigated sites. The proteomes displayed the prevalence of anaerobic metabolisms that were not directly related with petroleum biodegradation, indicating that in the absence of oxygen, biodegradation is significantly suppressed. This suppression was also suggested by examining the metabolome patterns. The proteome analysis further highlighted the metabolic coupling between methylotrophs and sulphate reducers in oxygen‐depleted petroleum‐polluted sediments.